DEVELOPMENT OF CRISPR-CAS9 DELIVERY SYSTEM BASED ON LIPID NANOPARTICLES TARGETED TO TGF-?1 GENE AND ACTIVITY TEST IN VITRO - Jummah, Nurul
Diabetic nephropathy (DN) is a microvascular disease triggered by hyperglycemic conditions that can lead to end-stage renal disease. A major obstacle in the conventional treatment of DN is the low effectiveness of drugs, as current therapies focus primarily on symptomatic relief rather than addressing the underlying cause of the disease. Transforming growth factor-beta 1 (TGF-?1) is a key factor in DN pathogenesis. This study explores the use of CRISPR-Cas9 nucleic acid-based therapy delivered via a targeted Lipid Nanoparticles (LNP) delivery system to reduce the expression of TGF-?1. An Enhanced Green Fluorescent Protein (EGFP) plasmid was utilized to confirm the ability of LNPs to deliver the pEGFP-C1 gene into the nucleus, with successful delivery observed using confocal microscopy. The pEGFP-C1 gene served as a model nucleic acid to optimize the LNP formulation for CRISPR-Cas9 delivery. To enhance LNP accumulation in target areas, surface modification was performed using polyethylene glycol (PEG), expected to increase circulation in vivo, thereby improving LNP accumulation at the target site. Human Embryonic Kidney (HEK) 293T cells, capable of expressing TGF-?1, were used as the cell model in this study. This research aimed to evaluate the CRISPR-Cas9 delivery system using LNP in terms of formulation and in vitro activity against the TGF-?1 gene in DN. The research involved LNP formulation, including optimization, characterization, safety testing on cells using CCK-8, cellular uptake studies, EGFP expression analysis, and circulation effect evaluation. The subsequent in vitro assays using HEK 293T cells measured target gene expression using qRT-PCR and ELISA. The particle size of blank LNP, PEG2000-DSPE-modified LNP, and pEGFP-C1 loaded PEG2000-DSPE-LNP ranged from 50-100 nm with particle charges of -10 to +10 mV. The polydispersity index values (<0.5) indicated good size uniformity. Entrapment efficiency of LNP-pEGFP-C1 was high at 91.62±3.895%. The LNP toxicity assay showed a safe concentration range (2.51-10.04 mM) with cell viability above 70%. Cellular uptake assays demonstrated endocytosis of LNP through caveolae, with 71,1% inhibition compared to the control, and successful nuclear entry confirmed by EGFP expression. v Subsequently, sgRNA was designed by targeting Ekson 3 of TGF-?1. sghTGFb1 was inserted in pUC57 plasmid and propagated in Escherichia coli Top 10. Then, the plasmids were characterized for size and sequence. Confirmed plasmids were restricted with XbaI enzyme, purified, and used as a template for in vitro transcription. The resulting sgRNA was complexed with Cas9 protein. Characterization of LNP-CRISPR-Cas9 showed particle sizes between 65.30- 105.40 nm, charges of -1.97 to -2.51 mV, and good size uniformity (polydispersity index <0.5). Circulation evaluation indicated an increased %ID/mL of blood with higher PEG2000-DSPE concentrations. In vitro gene expression analysis was conducted using LNP-CRISPR-Cas9, with qRT-PCR and ELISA techniques. Four formula variations (F1, F2, F3, and F4) were tested, each with Cas9: sgRNA ratios of 1:1, 1:2, 2:2, and 2:4. qRT-PCR analysis of TGF-?1 gene expression utilized the pfaffl method for calculating relative gene expression. Following LNP-CRISPR-Cas9 transfection, results showed a decrease in TGF-?1 gene expression by 39%, 67%, 75%, and 78% for F1, F2, F3, and F4, respectively, compared to those treated with blank LNP. ELISA analysis of TGF-?1 protein expression revealed decreases in %TGF-?1 of 0%, 16%, 7%, and 22% for F1, F2, F3, and F4, respectively. These analyses demonstrated that F4, followed by F2, provided better efficacy than the other formulations. Additionally, the results indicated that a Cas9:sgRNA ratio of 2:4 and 1:2 yielded better efficacy than 2:2 and 1:1. The results of this research are lipid nanoparticles-based delivery systems developed designed to be able to deliver several types of nucleic acids such as pDNA and the CRISPR-Cas9 system, with comparable delivery effectiveness to the nucleus in several types of cell lines that have never been studied before.